Unravelling the financial stability oversight council - El Mallah, Karim (2019)
The 2007-2008 financial crisis was a devastating on many households peaking global unemployment at 10% and dropping Global GDP by 5%. To deter another financial crisis the United States government passed the most complex and stringent legislation since the Great Depression of the 1930’s. The legislation created many agencies, and the ‘Financial Stability Oversight Council’, FSOC, was the most prominent agency that designated bank and nonbank financial institutions as ‘Systemically Important Financial Institutions’, or SIFIs. The designation mandates the organizations to adhere to extensive and costly ‘prudential standards’ and ‘enhanced supervision’. Several institutions were designated, however, only MetLife, Inc. fought its designation in the Court which led to rescinding, the remaining institutions designations followed. The focus of this work will be the introduction of the FSOC and its reasoning to the designation of MetLife along with the legal framework that took part in the court and led to the rescinding of MetLife’s designation along with the rescinding of other designations. The subject matter of this thesis is a good example of the reasonableness of laws & regulations.